Research progress on mechanical bowel preparation for elective colorectal surgery - Li Linjie; Sun Lingyu (结直肠肛门外科, 2022)
Bowel preparation not only affects the process of colorectal surgery but is also closely related to postoperative complications. In 2011, researchers suggested that mechanical bowel preparation (MBP) had no significant benefits compared to non-MBP in colon surgery. In recent years, enhanced recovery after surgery (ERAS) has been widely applied in clinical practice, leading to the gradual abandonment of traditional MBP for elective colorectal surgery. However, from the clinical practice experience of surgeons, MBP combined with oral antibiotic bowel preparation (OABP) before laparoscopic colorectal surgery is beneficial for intraoperative exposure of the surgical field and colonoscopy positioning. Recently, several scholars have proposed that MBP combined with OABP should be the "gold standard" for bowel preparation in elective colorectal surgery. This paper reviews the development history of surgical bowel preparation and analyzes the reasons for the inconsistent recommendations in guidelines for bowel preparation in elective colorectal surgery in Western countries. Additionally, based on many years of clinical practice experience, our team believes that preoperative MBP combined with OABP is still important and significant for patients undergoing elective colorectal surgery, especially those undergoing laparoscopic surgery, rectal surgery, needing intraoperative colonoscopy for positioning, or receiving transanal total mesorectal excision (taTME) or natural orifice specimen extraction surgery (NOSES).